The Prevalence of Video Games Addiction among Iraqi People in 2022 - Hashim, Hashim T.; Hashim, Ali Talib; Shah, Asghar; Shah, Jaffer; Tharwani, Zoaib Habib; Islam, Zarmina; Riaz, Mehr M. A.; Ahmad, Shoaib; Abd al Khudair, Mustafa Abd al Latif (Current Psychiatry Research and Reviews, 2024)
Background: Video game Addiction Disorder, in addition to other dependency disorders, seem to affect the pleasure center of the brain. The addictive behavior triggers a release of dopamine to promote the pleasurable experience activating the release of this chemical. Over time, more and more of the activity is needed to induce the same pleasurable response, creating a dependency. Methods: It is a cross-sectional study conducted among 2500 participants (more than 18 years) distributed in all the Iraqi provinces including both males and females. The questionnaire contains demographic questions and an internet addiction special validated questionnaire in the Arabic language. Results: The present study, comprising a predominantly male population (82%) showed a mild-moderate level of internet addiction among 93% of its participants (62% mild and 31% moderate), and an average internet usage score of 45. Race, particularly Kurdish, and the need to socialize were statistically significant predictors of video gaming. Twenty percent of participants in our study spent more than 3 hours a day playing video games using more than one device. The majority of these participants played racing (16%), platform (12%), and stealth (9.5%) video games. Conclusion: Everything is Internet-based. Adding an additional layer of confusion and distinction is that another digital technology is taking over the world as well – making access to computers even easier. But these benefits have a lot of consequences on humanity as well and it can cause an addiction especially to video games that are spreading among adolescents and early adults all over the world.
Keywords: Internet